Export-Led Growth Hypothesis: Comparison Between Islamic and Non-Islamic Countries in ASEAN - Ahmad Syarif (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2015)
This study aims to prove and analyze the effect of export growth on economic growth in the ASEAN countries. Using annual data from 2004 to 2014, the empirical result shows that export growth is significant and gives positive impact on the economic growth in ASEAN. However, investment and labor-force are less to affect the economic growth in ASEAN. This study also provides strong evidence that supports the hypothesis of export-led growth as described by Nurkse (Moon, 1997). Export-led growth is an economic strategy that is also used by Islamic countries in ASEAN. Export-led growth has two important reasons, it can generate profits and allow countries to balance their finances and the export growth can lead to greater productivity. This is consistent with the macro theory assumes that exports are injection to the economy (McCombie et al, 1994).